MODELING THE DYNAMIC IMPACT OF ECONOMIC FACTORS ON POULTRY MEAT PRODUCTION IN EGYPT - Ahmed A Mashaal; Gamal Eldin A. M. Ibrahim; Fatma Mabrouk (Journal of Animal and Plant Sciences, 2026)
The present paper examines key economic determinants affecting levels of commercial broiler (poultry) production using Autoregressive Distributed Lag (ARDL) to estimate short- and long-run effects on a sample data from 1995 to 2023, constraints that would limit the possibility for achieving full self-sufficiency or increased per capita availability, as well as identifying major challenges facing commercial broiler poultry sector in Egypt. The results show that there are economic factors affecting potential of self-sufficiency. The results of the study using the autoregressive distributed lag method over the period (1995-2023) indicated that there is a statistically significant positive relationship in the short term between the price of poultry in the current year and the quantity of broiler poultry production in the current year, and a statistically significant negative relationship between poultry investment in the previous year and the amount of broiler poultry production in the current year, and a statistically significant negative relationship between the inflation rate in the previous year and the quantity of broiler poultry production in the current year.This was due to the value of the error correction coefficient (ECt-1) which showed that the imbalance in the quantity of poultry meat produced could be corrected within the short term but the balance achieved in the long term within a period of less than two years. The long-term results showed a statistically significant negative relationship between the price of feed in the previous year and the quantity of broiler production in the current year, and a statistically significant negative relationship between the real per capita income in the last year and the amount of broiler production in the current year. The study recommends increasing investments in the poultry sector, as a 1% increase in investment leads to a long-term increase in broiler production of approximately 0.625%. The study also recommends expanding the application of inflation-control policies, as a 1% increase in inflation leads to decreases in broiler production of approximately 0.107% and 0.274% in the short- and long-term, respectively.
Keywords: Poultry meat; Poultry investment; Inflation rate; Self-sufficiency; ARDL